2016
DOI: 10.1167/iovs.15-18428
|View full text |Cite
|
Sign up to set email alerts
|

How Eye Dominance Strength Modulates the Influence of a Distractor on Saccade Accuracy

Abstract: We show that eye dominance strength influences saccade target selection. We discuss several arguments supporting the view that such advantage may be linked to the relationship between the dominant eye and ipsilateral hemisphere. French Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Ocular dominance is one of the important factors that could affect the results of saccadic eye movement. A previous study observed that eye dominance influenced saccade amplitude as the participants with strong ocular dominance reached more accurate saccades toward the target in the hemifield opposite to the side of dominant eye than in the same side (45). While our investigation has shown that both gaze direction and pupil position data can be used to evaluate latency and error rate of saccadic eye movement, ocular dominance as well as peak velocity of saccades could be evaluated with only gaze direction data.…”
Section: Evaluation Of Ocular Dominancementioning
confidence: 86%
“…Ocular dominance is one of the important factors that could affect the results of saccadic eye movement. A previous study observed that eye dominance influenced saccade amplitude as the participants with strong ocular dominance reached more accurate saccades toward the target in the hemifield opposite to the side of dominant eye than in the same side (45). While our investigation has shown that both gaze direction and pupil position data can be used to evaluate latency and error rate of saccadic eye movement, ocular dominance as well as peak velocity of saccades could be evaluated with only gaze direction data.…”
Section: Evaluation Of Ocular Dominancementioning
confidence: 86%
“…Interestingly, this shows that studies of NTAs in saccadic parameters could reveal individual characteristics such as the strength of eye dominance. Moreover, other studies contrasting participants with “strong” eye dominance (without any NTA in saccadic peak velocity) against participants with “weak” eye dominance (exhibiting standard NTA in saccadic peak velocity) showed that this measure of eye dominance strength based on oculomotor behaviour influenced perceptual (Chaumillon et al., ) and visuo‐motor (Tagu, Doré‐Mazars, Lemoine‐Lardennois, & Vergilino‐Perez, ) performance.…”
Section: Individual Variability In Ntasmentioning
confidence: 96%
“…In Tagu et al. () participants with left or right eye dominance made saccades towards a target presented along with a proximal distractor. This situation is known to induce a “global effect” (Findlay, ; Vitu, ; Walker et al., ): the saccade landing position falls in between the saccade target and the distractor.…”
Section: Individual Variability In Ntasmentioning
confidence: 99%
See 2 more Smart Citations